An Investigation of the Morphology of the Petrotympanic Fissure Using Cone-Beam Computed Tomography - Spyros Damaskos; Konstantinos Syriopoulos; Rogier L. Sens; Constantinus Politis (eJournal of Oral Maxillofacial Research, 2018)
Objectives: The purpose of the present study was: a) to examine the visibility and morphology of the petrotympanic fissure on cone-beam computed tomography images, and b) to investigate whether the petrotympanic fissure morphology is significantly affected by gender and age, or not.